Gender imaginaries in energy transitions: How professionals construct and envision gender equity in energy access in the Global South - Alda-Vidal, Cecilia; Khalid, Rihab; Foulds, Chris; Royston, Sarah; Greene, Mary (World development, 2023)
•Extends energy imaginaries ideas on gender equity and Global South transitions.•Integrates socio-technical and feminist approaches to energy and development.•Identifies Gender-Neutral Grid and Gender-Aware Decentralised Development Imaginaries.•Unpacks practices, key actors and outcomes of these imaginaries.•More needed on how professionals transform gendered inequities in energy access. The importance of gender is increasingly recognised in energy research, with growing awareness of the intersections of energy access and gender equity. Yet, a major knowledge gap exists regarding the role of professional intermediaries and institutions in reproducing and/or challenging gendered forms of energy exclusion, especially in the Global South. This paper addresses this gap by considering the gendered energy imaginaries of energy professionals in Global South contexts. Integrating literature on socio-technical imaginaries – which to date has been developed in predominantly Global North contexts – with feminist accounts of gender, energy and development, this paper investigates gendered imaginaries of energy access among energy professionals across four Global South contexts (India, Pakistan, Nigeria and Ghana). The case-study approach involved thematic analysis of interviews with 86 energy professionals, and revealed a spectrum of gendered energy imaginaries with two archetypes at the extremes of the spectrum: (1) The Gender-Neutral Grid Imaginary (GNGI); and, (2) The Gender-Aware Decentralised Development Imaginary (GADDI). These two imaginaries are unpacked in terms of their underlying actors, practices, and outcomes. Special attention is paid to how different constructions of the ‘end-user’ within professional imaginaries work to perpetuate or alleviate forms of gendered exclusion. These visions propagate energy access outcomes by shaping women’s access to and use of technologies, decision-making, and employment in the energy sector. Findings reveal that whilst the GADDI imaginary shows better considerations for gendered energy access, existing gendered imaginaries among professionals fall short across the spectrum in generating equitable outcomes. The paper concludes by providing specific recommendations for energy practice and policy dominating the energy transition landscape in the Global South and reiterates the need to move beyond ‘gender-mainstreaming’ towards intersectional conceptions of social equity and energy justice. This is vital to address the gaps in existing professional and institutional imaginaries that shape energy access outcomes.